A Field in Search of Theory and Respect: AE in the Mid-20th Century - Catherine A Hansman; Amy D Rose (Adult Education Research Conference, 2016)
The purpose of this paper is to analyze the development of an adult education professoriate and adult education programs in higher education in the 1950s and 1960s, as well as to examine the development of AERC as a means to advance and enhance theoretical knowledge related to the field.
Keywords: professoriate; program development; AERC; CPAE